The Development of a Flipbook-Based on Unggah – Ungguh for a Student at a Senior High School - Pratiwi, Adisti Dhea; Insani, Nur Hanifah (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop a digital learning medium in the form of a flipbook-based e-book to enhance the understanding of unggah-ungguh—the levels of speech in the Javanese language—among tenth-grade students at SMAN 1 Gebog Kudus. The research employed a development model adapted from Sugiyono, consisting of several stages: needs analysis, data collection, product design, expert validation, and product revision based on feedback. The validation results indicated that the Javanese unggah-ungguh flipbook-based e-book was feasible for use in learning, with positive evaluations in terms of content relevance, language clarity, visual design, and media usability. Moreover, the e-book was considered capable of increasing student interest in a topic that was previously seen as challenging and less engaging. The findings suggest that interactive digital learning media can serve as an innovative solution in Javanese language instruction, as they present materials in a more engaging and student-friendly manner, align with students' needs, and are compatible with technological advancements in today's educational landscape.